Antihypertensive and organ-protective effects of benazepril. (December 2010) - Barrios, Vivencio; Escobar, Carlos
Benazepril is a nonsulfhydryl ACE inhibitor with favorable pharmacodynamic and pharmacokinetic properties, well-established antihypertensive effects and a good tolerability profile. Recent clinical studies have demonstrated that patients treated with benazepril alone or in combination with hydrochlorothiazide or amlodipine may achieve beneficial renal outcomes that extend beyond blood pressure control. Furthermore, the recent Avoiding Cardiovascular Events Through Combination Therapy in Patients Living with Systolic Hypertension (ACCOMPLISH) trial showed decreased cardiovascular morbidity and mortality with benazepril when administered as a cotreatment. An additional novel therapeutic area for benazepril is atrial fibrillation. Differences between combination therapies have implications for which patients may be best suited to particular interventions, and further studies are required to fully ascertain this potential.